2011
DOI: 10.1007/s10943-011-9520-6
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of Religiousness/Spirituality: Implications for Health and Well-Being

Abstract: The purpose of this study was to develop empirically based typologies of religiousness/spirituality (R/S) and to determine whether the typologies were related to health and well-being. The study used a nationally representative sample of adults (N=1,431). Using latent profile analysis, typologies were derived based on religious service attendance, prayer, positive religious coping, and daily spiritual experiences. Multivariate statistical tests were used to examine cluster differences in health and well-being.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 32 publications
4
44
0
1
Order By: Relevance
“…Likewise, the spiritual intelligence dimensions play a significant role in predicting the quality of life of students. The findings of this research were coherent with similar studies on spiritual intelligence that is an effective factor in predicting the quality of life (Ahmad et al 2011;Bolghan-Abadi et al 2009Chamratrithirong et al 2010;Cotton et al 2009;Jafari et al 2010;Kliewer and Murrelle 2007;Moalemi et al 2010a, b;Park et al 2011;Rasic et al 2011;Shaw 2008;Wallace et al 2007). Shaw (2008) has studied the spirituality place in mental health and happiness.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Likewise, the spiritual intelligence dimensions play a significant role in predicting the quality of life of students. The findings of this research were coherent with similar studies on spiritual intelligence that is an effective factor in predicting the quality of life (Ahmad et al 2011;Bolghan-Abadi et al 2009Chamratrithirong et al 2010;Cotton et al 2009;Jafari et al 2010;Kliewer and Murrelle 2007;Moalemi et al 2010a, b;Park et al 2011;Rasic et al 2011;Shaw 2008;Wallace et al 2007). Shaw (2008) has studied the spirituality place in mental health and happiness.…”
Section: Discussionsupporting
confidence: 88%
“…Kliewer and Murrelle (2007) stated that personal belief in God affected on reducing the substance abuse among Central American countries adolescents. Park et al (2011) found that people who have high levels of religious/spirituality are most likely to be happy and satisfied with finances and are least likely to be psychological distressed. Malay Muslim Women with breast cancer, initially encountered with the possibility of dying, became sad, shocked and helpless.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature would suggest that R/S is positively related to both happiness (Mochon et al 2011;Park et al 2013) and subjective well-being (Green and Elliott 2010;Krause 2006).…”
Section: Hypothesesmentioning
confidence: 99%
“…In general, a positive relationship has been found between spirituality/religiousness and health in numerous controlled studies (Miller & Thoresen, 2003;Musgrave, Allen, & Allen, 2002;Park et al, 2013;Powell, Shahabi, & Thoresen, 2003;Seeman, Dubin, & Seeman, 2003). Nelson's stress buffering model (2009) explains the potential moderating, suppressor, and mediating roles of religiousness/spirituality.…”
Section: Extrinsic/intrinsic Religiousnessmentioning
confidence: 97%
“…Religiousness, on the other hand, is generally defined as a set of beliefs to which one ascribes in a community (Emmons & Paloutzian, 2003). Religiousness and spirituality are closely related, for religiousness is designed to foster one's spiritual life (Park et al, 2013).…”
Section: Extrinsic/intrinsic Religiousnessmentioning
confidence: 99%